1987
DOI: 10.2134/agronj1987.00021962007900060004x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Cycling in a Wheat Crop: Soil, Plant, and Aerial Nitrogen Transport1

Abstract: An understanding of N cycling in the soil‐plant‐atmosphere components of wheat (Triticum aestivum L.) production systems is necessary to maximize yield and quality. The objectives of this study were to examine N cycling and observe the effects of N surplus and deficit on N absorption/desorption in the soil and atmosphere and to evaluate translocation within the plant. Soil, plant, and microclimate measurements were taken concurrently, and soil, plant, and atmospheric ammonia (NH3) transport determined. During … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
106
0
10

Year Published

1993
1993
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(130 citation statements)
references
References 19 publications
14
106
0
10
Order By: Relevance
“…V C 2 3 7 2 5 2 9 1 1 2 activities of the enzymes glutamine synthetase (GS) and glutamine:2-oxoglutarateaminotransferase (GOGAT), the main compounds responsible for ammonia assimilation in the nitrogen metabolism of higher plants, resulting in an increase of the ammonia emission potential (Morgan & Parton, 1989). Using 15 N as a tracer, Harper et al (1987) demonstrated that after wheat anthesis, one half of the nitrogen in the grain came from a remobilization of N stored in stems and leaves during the breakdown process of proteins and amino acids during the maturation period of leaves and stems, while the other half came from the soil.…”
Section: Resultsmentioning
confidence: 99%
“…V C 2 3 7 2 5 2 9 1 1 2 activities of the enzymes glutamine synthetase (GS) and glutamine:2-oxoglutarateaminotransferase (GOGAT), the main compounds responsible for ammonia assimilation in the nitrogen metabolism of higher plants, resulting in an increase of the ammonia emission potential (Morgan & Parton, 1989). Using 15 N as a tracer, Harper et al (1987) demonstrated that after wheat anthesis, one half of the nitrogen in the grain came from a remobilization of N stored in stems and leaves during the breakdown process of proteins and amino acids during the maturation period of leaves and stems, while the other half came from the soil.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, regardless of how the process originated (absorption or fixation), N incorporation took place after anthesis (Table 4) and behaved like late cycle absorbed N, and could have influenced the dry matter and probably the duration of leaf area without changing grain production (Thomas et al, 1978;Gifford et al, 1984). Probably both capacity and quantity of reproductive sinks (grain) became a limiting factor, since they are defined at a stage much earlier than the extra availability of N (Moll et al, 1982;Harper et al, 1987;Mac Kown & Sanford, 1988).…”
Section: Fig 2 Effect Of Wheat (T Aestivum L Cv Br 23) Inoculatmentioning
confidence: 99%
“…Isto porque, nos estádios reprodutivos (pós-antese -início da senescência), há aumento do potencial de emissão de NH 3 devido às mudanças no metabolismo do N no vegetal, uma vez que ocorre maior clivagem de proteínas e aminoácidos nesses estádios (MORGAN & PARTON, 1989). HARPER et al (1987) (HOOKER et al, 1980). Dessa maneira, o NO 2 seria a fonte para a volatilização de NO 2 e NO x via corrente transpiratória, resultando em perdas de N via parte aérea das plantas.…”
Section: Resultsunclassified
“…No entanto, DAIGGER et al (1976), cultivando trigo de inverno, encontraram perdas que variaram de 25 a 80kg ha -1 entre a antese e a colheita. Na pós-antese na cultura de soja, foram encontradas perdas de 5,9 a 76,9kg ha -1 de N (HARPER et al, 1987;PAPAKOSTA & GAGIANAS, 1991). Durante a senescência foliar, que tem início após o florescimento, o aumento da hidrólise de proteínas é acompanhado pela redução nas atividades das enzimas glutamina sintetase (GS) e glutamato sintase (GOGAT), com o aumento de atividade da glutamato desidrogenase (GDH), principais responsáveis pela assimilação de NH 3 no metabolismo do nitrogênio nas plantas superiores.…”
Section: The Objective Of This Research Work Was To Evaluate the N Lounclassified